Contribuições para o processo de projeto de parques urbanos sob o olhar de dois arquitetos e urbanistas de Porto Alegre/RS - Covaleski, Joani Paulus (2020)
The city, composed of items that subsidize life in the urban environment, must offer open spaces that allow the realization of leisure and recreation activities. Urban parks, in several categories, are suitable areas and designed to meet this need, however, it is noted that there are inefficient or inadequate projects. In the scope of teaching, with a wide range of subjects in the Architecture and Urbanism courses, it is seen that not always the approach of projects of urban open spaces, in the park scale, is possible to be done, resulting in possible difficulties in the performance future graduates in this professional field. Thus, the research justification is introduced, which aims to contribute to the understanding of the design process of urban parks, from the perspective of two experts experienced in the area, together with indications found in the literature, in order to make the process of urban park design a better outlined activity, being less tied to uncertainties. These compiled contributions are intended to enable more assertive projects, minimizing errors and rework, optimizing time and facilitating the tracking of design flaws, thus cooperating for greater creative freedom and greater acceptance of the proposal by interested parties. Thus, the result consists of a synthesis of activities and tasks, grouped into three distinct phases, so that the proximity to the architectural design process is maintained, facilitating understanding and instructing the necessary process sequence. Research, in general, makes it possible for the designer, whether student or professional, to understand the necessary phases and remind him of suggested procedures that can be performed in the design process of urban parks.